THE CORRELATION OF MACRONUTRIENT INTAKE, NUTRITIONAL STATUS AND AGE OF MENARCHE WITH PRIMARY DYSMENORHORE - Maesaroh, Dena Ajeng; Sugiyanta, Sugiyanta; Nurmaida, Eny (UNIVERSITAS AIRLANGGA, 2025)
Background: Pain during menstruation that does not cause any abnormalities is called primary dysmenorrhea, while menstrual pain that is related to abnormalities in the pelvis is called secondary dysmenorrhea. According to data from WHO, 90% of women experience severe dysmenorrhea. The aim of this study was to find out the correlation between macronutrient intake, nutritional status, and age of menarche with primary dysmenorrhea in medical students at the University of Jember, Indonesia. Method: This type of research was carried out with a cross-sectional study design. The research was conducted online and carried out in December 2023-February 2024. Samples were taken using the proportionate stratified random sampling technique. The number of samples in this study was 79 pre-clinical female students. Data was obtained by respondents filling out Google Form and interviews via zoom to fill out the SQ-FFQ questionnaire. The analytical test used in this research is the Spearman test. Result: Correlation analysis showed there was no relationship between carbohydrate (p=0.518), fat (p=0.124) and protein (p=0.260) intake and primary dysmenorrhea. The correlation test of nutritional status with primary dysmenorrhea also produced a significance of 0.703 (p>0.05), which means there is no correlation. Correlation analysis of age of menarche with primary dysmenorrhea produced a significance of 0.003 (p<0.05), which means a correlation was found. Conclusion : No correlation was found between macronutrient intake and nutritional status and primary dysmenorrhea, and a correlation was found between age at menarche and primary dysmenorrhea.